The Plio-Pleistocene seepage history off western Svalbard inferred from 3D petroleum systems modelling - Daszinnies, Matthias Christian; Plaza-Faverola, Andreia; Sylta, Øyvind; Bünz, Stefan; Mattingsdal, Rune; Tømmerås, Are; Knies, Jochen (Marine and Petroleum Geology, 2021)
Methane seepage off the coast of Svalbard is demonstrated by active gas flares in the water column today and through precipitation of methane-derived authigenic carbonates (MDAC) over the past 160 000 years. Though submarine discharge of thermogenic methane is well documented, the geological history of past leakage is still debated, largely due to unconstrained free gas sources and seepage trigger mechanisms. We have assembled a high-resolution 3D petroleum systems model to evaluate the impact and charge of potential thermogenic hydrocarbons on the Vestnesa Ridge, NW Svalbard. We show that gaseous hydrocarbons, originating from Miocene age terrigenous organic matter, accumulates largely in ~2 million-year-old (Ma) sedimentary sequences underneath the pockmark system on the ridge's crest. These traps are constantly charged until present day. The supply of free gas to the gas hydrate stability zone (GHSZ) initiated the hydrate formation at ~3.0 Ma. We also show that gas leakage to the seafloor is governed by fault corruption of the hydrocarbon traps and not by excess pore fluid pressure. The onset of episodic seafloor seepage on Vestnesa Ridge can be associated with the first shelf edge glaciation of the Svalbard-Barents Sea ice sheet (SBIS), ~1.5 Ma ago. The results of the modelled petroleum system are consistent with the notion that repeated forebulge uplift and subsidence, due to cyclic SBIS build-up and decay, can be advocated as a mechanism that repeatedly caused extensional fracturing of the eastern Vestnesa Ridge segment. This fault damage affected modelled gas accumulations and led to the formation of hydrocarbon migration pathways to the seafloor. Repeated tapping into hydrocarbon reservoirs due to (a) fracture formation promoted by glacial isostatic adjustments (GIA) and (b) fracture re-activation could explain recent observations of multiple seepage events on Vestnesa Ridge during episodes of intense cooling over the past 160.000 years.